Contexts for Sustainable Implementation of a Colorectal Cancer Screening Program at a Community Health Center. Issue 1 (January 2016) - Yip, Mei-Po; Chun, Alan; Edelson, Jane; Feng, Xuaohua; Tu, Shin-Ping
Background . "Context" is a mediating construct that significantly influences the initiation and maintenance of program implementation, but it has seldom been studied in process evaluation. This case study describes the contextual factors that encourage or impede the implementation processes of a research-tested program at a Federally Qualified Community Health Center. Method . We conducted 14 key informant interviews with providers, nurses, medical assistants, and clinic staff in leadership and management positions during the 24 months of active implementation. Interview data were analyzed using Atlas.ti software. A written log documenting exposure, adherence, and coverage of the implementation was used to describe implementation fidelity. Results . Findings indicated that program implementation needs to align with the organization's mission and values. Sensemaking caused individuals to understand the importance of the new process and increased their motivation to follow assigned procedures. Revisions of the implementation process allowed the program to fit better with the clinic's existing workflow. However, permitting flexibility in the delivery of an intervention may result in inconsistent implementation fidelity. In this study, threats to implementation included unanticipated changes in the clinic environment, such as budget cuts to resources and staff turnover as a consequence of the current economic downturn. Conclusions . Momentum leading to sustainable implementation requires a continuous team effort and a stable environment; consequently, a successful implementation requires a structure that supports problem solving, communication, and evaluation.